Zmieniająca się rzeczywistość migrantów ukraińskich w Polsce (1991-2021) (Politeja, 2023)
THE CHANGING REALITY OF UKRAINIAN MIGRANTS IN POLAND (1991-2021)According to the 2019 survey of migrants from Ukraine to Poland, the causes and prospects of their migration in categories of ‘ejection’ from the donor country and ‘attraction’ to the recipient country are analyzed. It was found that the reasons for relocation do not correlate with the respondents’ assessment of the prospects they had opened in Poland. We assume that this is a consequence of the reactive nature of migration decisions related to the survival values over the values of self-realization.